Climate change – to act or not to act - Abdul Razak, Dzulkifli (Sun Media Corporation Sdn Bhd, 2019)
THE choice of TIME’s Person of the Year is likely to (re)define what 2020 is all about. Greta Thunberg has been quoted saying that it will be the year for action on climate change. Coming at the heels of COP25 which had to do some extended work in Madrid despite a two-week session, it gave the impression that she might be right. It lends credence to her call for action given the on-again, off-again reception from world leaders in their recent deliberations. There has been frustration and disappointment all round, including the UN secretary-general.